ASSESSMENT OF PROFESSIONAL’S ADHERENCE TO JOINT NATIONAL COMMITTEE 8 GUIDELINES IN THE MANAGEMENT OF HYPERTENSION - D’SOUZA, SCHNELL JENNIFER; Mani, Ancel Neethu; Kurian, Nimisha; C, Jaikanth (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: Hypertension is the most insidious ailment in primary care with its management being a daily affair. The avail of antihypertensive medications has affirmed their efficacy in blood pressure alleviation. Yet, the methodical choice of medication with which treatment ought to commence at the precise blood pressure threshold and maintained at a target level was undiscerned. Consequently, the Eighth Joint National Committee grants an evidence-based tool, which was employed in the appraisal of professional's adherence to joint national committee 8 guidelines. Methods: A prospective, observational study was governed. Aggregate patients with hypertension with/without diabetes mellitus (DM) and/ or chronic kidney failure admitted in general medicine and the dialysis unit of the tertiary health care hospital, for 4 months were enrolled. The rationality of antihypertensive medications and target blood pressure was noted. Results: Patients matriculated to 125, 90 males and 35 females. Average age perceived was between 51 and 60 years, with the length of stay 14.39 (standard deviation [SD]Â±1.52) and 9.3 (SDÂ±0.46) days in the respective unit. The gross medication endorsed represents 1085 medications, incorporating 337 antihypertensive medications. The optimal choice of an antihypertensive medicine was clonidine and amlodipine. Adherence in the populace with lone hypertension was cent percent, trailed by hypertension with DM 82.35% and minimal in hypertension with chronic kidney disease. Conclusion: 86-medication compiled adherence to the guidelines (25.52%). Rationality of medication depicts 25.6% were rational and 73.6% distinguish as non-rational, amid a demise of a sole victim. A significant high-grade defiance of health-care practitioners to the Eighth Joint National Committee guidelines was evidenced from our study.